Strategies for Relapse Prevention in Acute Myeloid Leukemia - Runneberger, Isabel (My University, 2018)
Acute myeloid leukemia(AML)is the most common form of acute leukemia in adults and is characterized by rapid accumulation of leukemic blasts in bloodand bone marrow. Genetically, AML is a heterogenous disease where a variety of mutations or translocations drive the disease. The most frequent molecular abnormality in AML is caused by mutations in NPM1. AML is treated with high doses of chemotherapy in induction and consolidation cycles. While most patients respond to the intitial treatment,the majority of patients will relapse. Only 30-40% of adult patients reach long-term survival. The bone marrow microenvironment has been suggested to provide protection for leukemic cells against chemotherapy, resulting in residual leukemic cells that are believed to be responsible for relapses if they start to proliferate again. Recent studies indicate that stromal cells within the bone marrow may transfer mitochondria to leukemic cells and partly protect the leukemic cells against chemotherapy. Reactive oxygenspecies(ROS)were proposed to favor mitochondrial transfer. ROS have previously been shown to limit myeloid diﬀerentiation in AML. In this thesis we have further explored the role of ROS,including NADPHoxidase2(NOX2)-derived ROS, during myeloid diﬀerentiation in AML and mitochondrial transfer between stromal and AML cells. We show that inhibition of NOX2-derived ROS in AML cells triggered their diﬀerentiation, but did not aﬀect their capacity to initiate long-term colonies. Furthermore, our data indicated that mitochondria could be transferred from stromal to AMLcells,but we did not observe any eﬀect of ROS on the transfer. A parallel aim was to explore the possibility of expanding and isolating NPM1mut speciﬁc CD8+ T cells, as such cells potentially could be utilized to target and eradicate residual leukemic cells for patients with NPM1mut AML. Using more common antigens, we optimized a protocol to expandand detect antigen-speciﬁc Tcells from healthy blood donors. The protocol was used to initiate studies to expand and detect NPM1mut-speciﬁc CD8+ T cells using NPM1mut-speciﬁc tetramers. Our initial results indicate that it is possible to detect NPM1mut-speciﬁc CD8+ T cells from healthy donors, but that this is a very rare cell population.
Keywords: Cell- och molekylärbiologi; Immunologi inom det medicinska området; Hematologi; Livsvetenskaper; Cell and Molecular Biology; Immunology in the medical area; Hematology; Life Science